Mind the gap: diversity and reactivity relationships among multihaem cytochromes of the MtrA/DmsE family. (21st November 2012) - Bewley, Kathryn D.; Firer-Sherwood, Mackenzie A.; Mock, Jee-Young; Ando, Nozomi; Drennan, Catherine L.; Elliott, Sean J.
Abstract : Shewanella oneidensis MR-1 has the ability to use many external terminal electron acceptors during anaerobic respiration, such as DMSO. The pathway that facilitates this electron transfer includes the decahaem cytochrome DmsE, a paralogue of the MtrA family of decahaem cytochromes. Although both DmsE and MtrA are decahaem cytochromes implicated in the long-range electron transfer across a ~300 Å (1 Å=0.1 nm) wide periplasmic 'gap', MtrA has been shown to be only 105 Å in maximal length. In the present paper, DmsE is further characterized via protein film voltammetry, revealing that the electrochemistry of the DmsE haem cofactors display macroscopic potentials lower than those of MtrA by 100 mV. It is possible this tuning of the redox potential of DmsE is required to shuttle electrons to the outer-membrane proteins specific to DMSO reduction. Other decahaem cytochromes found in S. oneidensis, such as the outer-membrane proteins MtrC, MtrF and OmcA, have been shown to have electrochemical properties similar to those of MtrA, yet possess a different evolutionary relationship.